2014
DOI: 10.7717/peerj.404
|View full text |Cite
|
Sign up to set email alerts
|

Tree mortality from a short-duration freezing event and global-change-type drought in a Southwestern piñon-juniper woodland, USA

Abstract: This study documents tree mortality in Big Bend National Park in Texas in response to the most acute one-year drought on record, which occurred following a five-day winter freeze. I estimated changes in forest stand structure and species composition due to freezing and drought in the Chisos Mountains of Big Bend National Park using permanent monitoring plot data. The drought killed over half (63%) of the sampled trees over the entire elevation gradient. Significant mortality occurred in trees up to 20 cm diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…). It is also consistent with patterns of mortality associated with long‐term drought interacting with sporadic freeze–thaw events to increase mortality rates in Pinus cembroides and Juniperus deppeana (Polous ) and multiple co‐existing Juniperus species due to xylem embolism (Willson and Jackson ). Because of this interaction between a background stressor (gradual loss of snow or occasional drought) and a sporadic weather event (in the examples, thaw and freezing events), this mortality is not expected every year.…”
Section: Discussionsupporting
confidence: 73%
“…). It is also consistent with patterns of mortality associated with long‐term drought interacting with sporadic freeze–thaw events to increase mortality rates in Pinus cembroides and Juniperus deppeana (Polous ) and multiple co‐existing Juniperus species due to xylem embolism (Willson and Jackson ). Because of this interaction between a background stressor (gradual loss of snow or occasional drought) and a sporadic weather event (in the examples, thaw and freezing events), this mortality is not expected every year.…”
Section: Discussionsupporting
confidence: 73%
“…Q. emoryi may still be pushed downslope from its optimal elevation zone. It was found to be more vulnerable to drought‐induced mortality than either Q. grisea or Q. arizonica in a long‐term drought in Texas (Poulos ). Among the white oaks, Q. rugosa has been found to be a relatively shade‐tolerant species (Poulos et al.…”
Section: Discussionmentioning
confidence: 99%
“…Q. emoryi may still be pushed downslope from its optimal elevation zone. It was found to be more vulnerable to drought-induced mortality than either Q. grisea or Q. arizonica in a long-term drought in Texas (Poulos 2014). Among the white oaks, Q. rugosa has been found to be a relatively shade-tolerant species (Poulos et al 2008), which may allow it to live a similarly conservative evergreen lifestyle at the middle elevations of the white oak gradient, while its relatives demonstrate different timing of deciduousness.…”
Section: Species Coexistence and Niche Partitioning Within Subgeneramentioning
confidence: 99%
“…A study of the pinyon-juniper stands in Big Bend National Park, found that P. cembroides had the highest tree mortality followed by J. deppeana, and Q. emoryi, resulting from a combined stress of a severe winter freeze event and the 2011 drought (Poulos, 2014). A study of the pinyon-juniper stands in Big Bend National Park, found that P. cembroides had the highest tree mortality followed by J. deppeana, and Q. emoryi, resulting from a combined stress of a severe winter freeze event and the 2011 drought (Poulos, 2014).…”
Section: Discussionmentioning
confidence: 99%